Argumentação e político em enunciações da escravidão - Silvério, Nirce Aparecida Ferreira (Universidade Federal de São Carlos, 2018)
This thesis develops a semantic study and approaches argumentative movements related to slavery both at the end of the XIX century, as at present. We analyze print and digital media, texts from late 19th century newspapers and texts from current websites. We discuss the hypothesis that: just as there are religious, legal, socio-historical arguments that indicate / guide the end of slavery there are those who prescribe, regulate, justify and perpetuate it. And these arguments are sometimes explicitly immersed in silence that conceals an argumentative orientation and argumentation of permanence (or extinction) of slavery. We also have a sub-hypothesis: a social place of saying argues based on the argumentativeness that is put into operation due to the argumentation and this makes emerge words that produce effects and are exposed to the drift of the senses, which can produce the ( s) anticipated direction (s) or other (s). Some of our questions were: do people allow themselves to be enslaved? How is slavery signified in the argumentative movements and games of sayings in the utterances we analyze? The three clusters we took to analyze: a) the newspaper O Abolicionista, b) the Correio Paulistano newspaper, c) the texts of sites; have led us to different semantic meanings for the word slavery, which, however, have a common background signified by its memorable in relation to the present and futurity. We are based on the semantics of the event, created by the Brazilian researcher Eduardo Guimarães, and with contributions from discourse analysis, in which the argument is studied differently from rhetorical studies and argumentation in the Ducrot language. We explore the argumentation and the political from the enunciative scenes that particularize the space of enunciation and look for designations that indicate games of forces and enunciative processes that inscribe silencings. Thus, we do not only work with the argumentative directives of a speaker to an allocutionary one, but we also seek the positions sustained in the argumentation and the interpretation of the set of enunciative scenes in integration. We then identify: the space of enunciation of the legal validity of slavery in Brazil and the space of enunciation of slavery in the present, in the first, we saw a relation with the space of English enunciation, determining the meanings of slavery, abolition and what words like abolitionist, emancipation and manumission present contradictory meanings that give us other aspects of its functioning; in the second, we see the effects of the memorable of slavery determining the criada, sinhazinha, the designation of contemporary slavery, besides presenting us with a slave in Brazil, which is no longer only the Negro, which is now determined in juridical discourse, excludes processes of silencing of enslavement in the present time.
Argumentation and politics in enunciations of slavery
Argumentación y político en enunciaciones de la esclavitud
Keywords: Argumentação; Semântica do acontecimento; Escravidão; Século XIX e atualidade; Político; Argumentation; Semantics of the event; Slavery; 19th century and actuality; Political; Argumentación; Semántica del acontecimiento; Esclavitud; Siglo XIX y actualidad; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA